Internet Usage and Its Addiction Level among Students in a Selected College in Ras Al Khaimah Emirate: A Cross-Sectional Study (International Journal of Studies in Nursing, 2019)
Background and aim: The internet is a worldwide area network that connects computer system throughout the world providing a variety of information and communication. Internet addiction is defined as any online-related, compulsive behavior which interferes with normal living and causes severe stress on family, friends, loved ones, and one's work environment. Aim: This study assessed the internet usage and its addiction level among university students in a selected university in Ras Al Khaimah, United Arab Emirate. University students are highly predisposed to internet addiction which can affect their personal, family, educational, interactive and societal life. Study design: A cross-sectional design .The sample of the study consisted of 110 nursing students who were selected using convenient sample. Internet addiction test, internet usage questionnaire and student attitude scale were used as data collection instruments. Results: The findings showed that more than half (50.9%) of students were aged 21-